Financiamento para micro e pequenas empresas: uma análise do perfil quanto à liberação de crédito - Nogueira, Alisson Ferreira (Universidade Federal Rural do Semi-Árido, 2020)
Brazilian micro and small enterprises, unlike the big ones, face some obstacles when it comes to credit access and loan. In light of this, there has arisen a need for investigating such a scenario. Said that, the main goal of this research were to describe the Financial and economic scenario refering to the credit granting and application of micro and small enterprises. Beyond that, the study was sectioned in some specific goals, such as: describing the types of funding and how the credit is applied by micro and small enterprises; talking about the difficulties faced in order to be given credit access; describing the types of guaranties required by credit providers. To make such analisys, a cross sectional descriptive research had been performed on qualitative-quantitative basis. The sample was composed by 269 companies and the data was gathered by a Junior Company from the Business Management course from UFERSA. The results show that over a half of the interviewees don't benefit from any of the financing types mentioned in this study; high interest rates are the main difficulty source; not being able to present a security before the Financial Institutions is a common situation exposed by 21,2% of the respondents.
Keywords: Micro empresa; Pequena empresa; Financiamento; Crédito; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO